Integration of Tradition and Sharia: Dowry and Dui Menre in the Marriage of the Bugis Community in Bone Regency - Nur Avita; Ahmad Rusyaid Idris; Frina Oktalita (Institut Agama Islam Negeri Palangka Raya, 2022)
A Mahr (Dowry) and dui menre become interesting phenomenon that occurs in the marriage practice of the Bugis community in Bone Regency. The higher the social status of the prospective wife's family, the higher the dui menre. When an agreement has been reached on the amount of dui menre, then the husband will give a dowry in the marriage contract. Both of these things must be fulfilled as the requirement for marriage. When the husband does not fulfill the dui menre as previously agreed on the agreement, the marriage process might not occur. The study aimed to integrate tradition and sharia in the marriage of the Bugis community in Bone Regency. The research was empirical legal research with a socio-legal approach. The study indicated that the dowry and dui menre in Bugis traditional marriages are an inseparable. Here, the integration is dui menre as a pre-marital condition that must be fulfilled in the context of giving as a form of respect and assistance to the prospective wife’s family. There is no prohibition in Islam as long as there is an agreement between the two parties, and no violate the sharia principles. Meanwhile, the dowry is also obligatory and carried out in the marriages of the people of the Bone regency. Therefore, the dowry and dui menre in the marriage of the Bone community are following the tradition and sharia.